2018
DOI: 10.1200/jco.2018.77.8589
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk for Subsequent Neoplasms Among Long-Term Survivors of Childhood Cancer

Abstract: Purpose Childhood cancer survivors are at increased risk of subsequent neoplasms (SNs), but the germline genetic contribution is largely unknown. We assessed the contribution of pathogenic/likely pathogenic (P/LP) mutations in cancer predisposition genes to their SN risk. Patients and Methods Whole-genome sequencing (30-fold) was performed on samples from childhood cancer survivors who were ≥ 5 years since initial cancer diagnosis and participants in the St Jude Lifetime Cohort Study, a retrospective hospital-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
107
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 26 publications
(9 reference statements)
7
107
1
1
Order By: Relevance
“…All other 408 exclusion criteria, adjustment covariates, and case/phenotype definitions were identical to those applied 409 to the SJLIFE analysis. The SJLIFE genotype data used in this analysis was collected as a part of larger effort to 423 sequence whole genomes of SJLIFE participants 40 . Comprehensive details of DNA sample collection, 424 extraction, sequencing, quality control, and variant mapping have been described previously 40,41 .…”
Section: Ccss Cohort 390 391mentioning
confidence: 99%
See 1 more Smart Citation
“…All other 408 exclusion criteria, adjustment covariates, and case/phenotype definitions were identical to those applied 409 to the SJLIFE analysis. The SJLIFE genotype data used in this analysis was collected as a part of larger effort to 423 sequence whole genomes of SJLIFE participants 40 . Comprehensive details of DNA sample collection, 424 extraction, sequencing, quality control, and variant mapping have been described previously 40,41 .…”
Section: Ccss Cohort 390 391mentioning
confidence: 99%
“…The SJLIFE genotype data used in this analysis was collected as a part of larger effort to 423 sequence whole genomes of SJLIFE participants 40 . Comprehensive details of DNA sample collection, 424 extraction, sequencing, quality control, and variant mapping have been described previously 40,41 . Briefly, 425 sequencing for 3,006 samples was completed at the HudsonAlpha Institute for Biotechnology Genomic 426 Raw intensity data was processed with the "minfi" R package 51 , including sample and probe 473 quality controls, background correction, and normalization.…”
Section: Ccss Cohort 390 391mentioning
confidence: 99%
“…Cancer July 15, 2019 In pediatric oncology, a significant proportion of children with cancer (9%-12%) [5][6][7] carry a germline mutation in 1 or more cancer predisposition genes prompting recommendations for the consideration of germline genetic testing. However, germline sequencing is not without its potential risks, and many professional guidelines recommend against broadly testing children for heritable genetic conditions that have no actionability in childhood.…”
Section: Introductionmentioning
confidence: 99%
“…A similar pattern has been observed when considering the contribution of SMNs to the total number of chronic conditions experienced per survivor, where NHL survivors have been reported to experience a lower cumulative burden of SMNs relative to many other survivor groups (Bhakta et al , ). Despite these findings, Wang et al () identified unique patterns and prevalence of pathogenic or likely pathogenic mutations in cancer predisposition genes in NHL survivors, suggesting that further work is necessary to understand the underlying aetiology of SMN risk, as well as potential genetic associations with other late adverse health effects.…”
Section: Subsequent Malignant Neoplasmsmentioning
confidence: 99%